Temporal relationships between systemic lupus erythematosus and comorbidities. (19th December 2018) - Kuo, Chang-Fu; Chou, I -Jun; Rees, Frances; Grainge, Matthew J; Lanyon, Peter; Davenport, Graham; Mallen, Christian D; Chung, Ting-Ting; Chen, Jung-Sheng; Zhang, Weiya; Doherty, Michael
Abstract: Objective: To examine the burden of comorbidities prior to and after the diagnosis of SLE and its impact on mortality. Methods: We identified 1605 incident cases of SLE and 6284 matched controls from the UK primary care. The risks of comorbidities before (prevalence; odds ratios) and after SLE diagnosis (incidence; hazard ratios) and the impact of comorbidities at diagnosis on all-cause mortality were estimated. Results: At diagnosis, SLE was associated with adjusted odds ratios (95% CI) of 2.25 (1.97–2.56), 3.37 (2.49–4.57) and 3.54 (1.89–6.63) for a Charlson comorbidity index of 1–2, 3–4 and ≥5, respectively. Following diagnosis, SLE also associated with increased risk of developing any comorbidity with an adjusted hazard ratio (95% CI) of 1.30 (95% CI, 1.13–1.49). At diagnosis, SLE was associated with a greater risk of cancer, cardiovascular, renal, liver, rheumatological and neurological diseases as well as depression, anaemia and psoriasis. Risks of developing incident comorbidity in the categories of neoplasm, cardiovascular, genitourinary, metabolic/endocrine, gastrointestinal and hepatic diseases, chronic pulmonary diseases, musculoskeletal/connective tissue and neurological diseases were higher in SLE patients. People with SLE had higher mortality risk compared with controls, with adjusted hazard ratio of 1.91 (95% CI, 1.62–2.26); after further adjusting for comorbidities this reduced to 1.64 (1.37–1.97). Comorbidities at SLE diagnosis accounted for 27.6% of the apparent difference in mortality between SLE patients and matched controls. Conclusion: People with SLE have increased risks of multiple comorbidities both prior to and after diagnosis and this contributes significantly to all-cause mortality.